(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Mobile Adhoc Networks (MANETs), the route discovery phase involves with a huge flooding overhead due to the propagation of route request packets without any constraints. The redundant flooding packets lead to dramatic deterioration of the network performance. Location constraint-based flooding is one possible solution to reduce the flooding overhead. In this paper, we propose an Adaptive Location Aided Routing which is adaptive for varying topology and varying node density. This method aims at the determination of an optimal network portion (called as Request zone) which lessens the flooding overhead by allowing only few nodes to rebroadcast the request packets. The request zone is determined based on location coordinates and communication rage of source and destination nodes. Once the request zone is derived, the source node appends the coordinates of request zone and broadcasts the request packets. For any node which lies in the request zone, it rebroadcasts the request packet otherwise it simple drops the packet. An extensive simulation experiments are conducted, and the performance is assessed with Routing Overhead and Route Discovery delay with varying network parameters.